Case Report: SMARCA4 (BRG1)-deficient undifferentiated carcinoma of gallbladder with genetic analysis - Meng, Xiangpeng; Ma, Jia; Meng, Nan; Yun, Tianyu; Niu, Beifang (Frontiers in Oncology, 2023)
SMARCA4 (BRG1)-deficient undifferentiated carcinoma is a rare and highly aggressive malignancy. It has been reported to occur in a multiple range of organs. However, to the best of our knowledge, SMARCA4 (BRG1)-deficient undifferentiated carcinoma of gallbladder has not yet been reported. Here, we describe a case of SMARCA4 (BRG1)-deficient undifferentiated carcinoma of gallbladder. Through comprehensive genetic analysis, we hypothesized that in addition to SMARCA4 (BRG1) deficiency, other genetic changes might also be involved in the tumorigenesis of undifferentiated gallbladder cancer in this patient, particularly somatic mutations in the CTNNB1, KRAS, PIK3CA, TP53, CREBBP, and FANCI genes. To the best of our knowledge, this is the first report of SMARCA4 (BRG1)-deficient undifferentiated carcinoma of gallbladder with genetic analysis.